A fair and progressive carbon price for a sustainable economy. (1st February 2022) - Boroumand, Raphaël-Homayoun; Goutte, Stéphane; Porcher, Thomas; Stocker, Thomas F.
Abstract: The principle of "common but differentiated responsibility", as a key concept of the United Nations Framework Convention on Climate Change (UNFCCC), acknowledges the conditions for a generally acceptable and differentiated pricing mechanism on carbon emissions. With reference to this principle, carbon price determination has become a necessary instrument for sustainable policies. Considering the development gaps and the historical responsibility of the OECD's countries, a single carbon price would raise a major issue of equity between "developed" and "developing" countries. Although from a climate perspective each molecule of CO2 produces the same level of damage despite the nature or the location of the activity generating the emissions, all CO 2 emissions are not on an equal footing. Indeed, some are necessary to improve the lives of people in "developing" countries when others can be considered not indispensable, especially beyond a certain level of development. In this policy paper, we explain how the price of carbon should be fixed according to a reference price depending on the Human Development Index (HDI) and CO 2 emissions per capita. The HDI criterion enables to integrate progressivity into taxation while distinguishing what is essential from what is not. By taking a reference price based on the HDI, countries with low HDIs should pay a lower carbon price. However, with same HDI levels, countries with higher CO2 emissions should pay a penalty on the reference price. Our policy paper analyses the benefits of a differentiated and progressive carbon pricing mechanism to facilitate intergovernmental cooperation for a more sustainable economy. Highlights: This policy paper analyses the benefits of a differentiated and progressive carbon pricing. The article proposes carbon prices based on the Human Development Index (HDI) and C 0 2 emissions per capita. The proposed mechanism is an efficient mean to facilitate intergovernmental cooperation and modify the global energy mix for a sustainable growth.